Development of Eco-Charger with Solar Power in Airport - Soleh, Asep Muhamad; Handayani, Ni Putu Heni (Universitas Dharma Wacana, 2025)
Renewable Alternative Energy is a very important issue due to global climate issues. In the 2021 United Nations General Assembly, the President of the Republic of Indonesia, in his speech, supported the development of renewable energy and stopped the development that uses coal as an energy source. Airports, as one of the infrastructures that use very large amounts of electrical energy, currently rely heavily on electrical energy, which still uses coal as fuel. The research method used is research and development (R&D), which has been carried out at the Politeknik Penerbangan Palembang since August 2021. The research we conducted produced an eco-charger with solar power as a power source and a battery as a medium for storing electrical energy controlled by a solar charge controller module. This research involved cadets in the development process so it also supports project-based learning. This eco charger's power source can be used for twenty-four hours non-stop because the source of electrical energy is stored in the battery. During the day, the battery will be charged with electrical energy from the solar panel and automatically stop charging if the battery is full. This eco charger is used to charge mobile phones at airports and can also be used in other places such as bus stops, bus terminals, and train stations.